Note-Taking Skill Among Bilingual Students in Academia: Literacy, Language and Cognitive Examination - Asaly-Zetawi, Mona; Lipka, Orly (Frontiers in Psychology, 2019)
The ability to take notes while listening to a lecture is important and complicated. The main goal of the current study was to examine note-taking skills among students with a first language of Hebrew (L1) and students with a first language of Arabic and Hebrew as a second language (L2). Literacy, language, cognitive, and note-taking skills were assessed among 63 undergraduate students (28 L1). L1 students were found to produce notes of higher quality than did L2 students. Moreover, there were significant differences between the groups on measures of vocabulary, word reading fluency, and handwriting speed. The results also revealed that first language was the most important variable in predicting note quality, followed by word reading fluency. Educational implications and directions for further research are discussed in light of the findings.